Physico-chemical characterization of bilirubin-10-sulfonate and comparison of its acid-base behavior with unconjugated bilirubin - Čepa, Adam; Dejmková, Veronika; Lešetický, Ladislav; Jelínek, Ivan; Smrček, Stanislav; Štícha, Martin; Jašprová, Jana; Urbanová, Marie; Goncharova, Iryna; Dračínský, Martin; Procházková, Eliška; Ostrow, Donald J; et al. (Scientific reports, 2021)
Unconjugated bilirubin (UCB) is the end-product of heme catabolism in the intravascular compartment. Although beneficial for human health when mildly elevated in the body, when present at greater than a critical threshold concentration, UCB exerts toxic effects that are related to its physico-chemical properties, particularly affecting the central nervous system. The aim of the present study was to characterize bilirubin-10-sulfonate (ranarubin), a naturally occurring bile pigment, including determination of its mixed acidity constants (pKa*). Thanks to the presence of the sulfonic acid moiety, this compound is more polar compared to UCB, which might theoretically solve the problem with an accurate determination of the UCB pKa* values of its propionic acid carboxylic groups. Bilirubin-10-sulfonate was synthesized by modification of a previously described procedure; and its properties were studied by mass spectrometry (MS), nuclear magnetic resonance (NMR), infrared (IR), and circular dichroism (CD) spectroscopy. Determination of pKa* values of bilirubin-10-sulfonate and UCB was performed by capillary electrophoresis with low pigment concentrations in polar buffers. The identity of the synthesized bilirubin-10-sulfonate was confirmed by MS, and the pigment was further characterized by NMR, IR, and CD spectroscopy. The pKa values of carboxylic acid moieties of bilirubin-10-sulfonate were determined to be 5.02, whereas those of UCB were determined to be 9.01. The physico-chemical properties of bilirubin-10-sulfonate were partially characterized with low pKa* values compared to those of UCB, indicating that bilirubin-10-sulfonate cannot be used as a surrogate pigment for UCB chemical studies. In addition, using a different methodological approach, the pKa* values of UCB were found to be in a mildly alkaline region, confirming the conclusions of a recent critical re-evaluation of this specific issue.